Experience With Pretravel Testing for SARS-CoV-2 at an Academic Medical Center - Katherine L. Imborek MD; Matthew D. Krasowski MD, PhD; Paul Natvig MD; Anna E. Merrill PhD; Daniel J. Diekema MD; Bradley A. Ford MD, PhD (Elsevier, 2021)
International travel has been a significant factor in the coronavirus disease 2019 pandemic. Many countries and airlines have implemented travel restrictions to limit the spread of the causative agent, severe acute respiratory syndrome coronavirus-2. A common requirement has been a negative reverse-transcriptase polymerase chain reaction performed by a clinical laboratory within 48 to 72 hours of departure. A more recent travel mandate for severe acute respiratory syndrome coronavirus-2 immunoglobulin M serology testing was instituted by the Chinese government on October 29, 2020. Pretravel testing for severe acute respiratory syndrome coronavirus-2 raises complications in terms of cost, turnaround time, and follow-up of positive results. In this report, we describe the experience of a multidisciplinary collaboration to develop a workflow for pretravel severe acute respiratory syndrome coronavirus-2 reverse-transcriptase polymerase chain reaction and immunoglobulin M serology testing at an academic medical center. The workflow primarily involved self-payment by patients and preferred retrieval of results by the patient through the electronic health record patient portal (Epic MyChart). A total of 556 unique patients underwent pretravel reverse-transcriptase polymerase chain reaction testing, with 13 (2.4%) having one or more positive results, a rate similar to that for reverse-transcriptase polymerase chain reaction testing performed for other protocol-driven asymptomatic screening (eg, inpatient admissions, preprocedural) at our medical center. For 5 of 13 reverse-transcriptase polymerase chain reaction positive samples, the traveler had clinical history, prior reverse-transcriptase polymerase chain reaction positive, and high cycle thresholds values on pretravel testing consistent with remote infection and minimal transmission risk. Severe acute respiratory syndrome coronavirus-2 immunoglobulin M was performed on only 24 patients but resulted in 2 likely false positives. Overall, our experience at an academic medical center shows the challenge with pretravel severe acute respiratory syndrome coronavirus-2 testing.